Scuba Diving Tourism System: A framework for collaborative management and sustainability. (April 2015) - Dimmock, Kay; Musa, Ghazali
Abstract: This paper proposes a conceptual model for the scuba diving tourism system (SDTS). A holistic view was adopted to highlight the central elements of scuba diving tourism (SDT). Specifically, the paper examines the key components in the SDTS along with issues which challenge the sustainability of SDT. Scuba divers, the marine environment, the host community and the scuba diving tourism industry (including all associated industries) are fundamental elements of the SDTS. Notably, the host community is often overlooked as a key stakeholder in the management and sustainability of SDT at the destination. A systems approach used to conceptualise the SDTS highlights the need for adaptive management and leadership to encourage future orientated thinking and the integration of stakeholder concerns and perspectives to ensure the sustainability of marine resources and experiences.